And if the time to passes relatively different for insects? Unfolding of Einstein’s Theory of Relativity: the dilation of time to different systems of inercial references as a function of the inercial mass. - Macedo, Mariel dos Santos (Open Science Journal, 2023)
The purpose of this insight is to contribute to a possible development of Einstein's theory of relativity. Starting from the idea that gravitational fields deform the space-time fabric, affecting objects as a function of inertial mass. Thus, two objects or ecosystems equidistant from the same field, with significant differences in inertial masses, would also be subject to the same relativistic effects. O objetivo deste insight é contribir para um possível desdobramento a teoria da relatividade de Einstein. Partindo da ideia de que se os campos gravitacionais deformam o tecido espaço-temporal afetando os objetos em função da massa inercial. Assim, dois objetos ou ecossistemas equidistânciantes de um mesmo campo, com significativas diferenças nas massas inerciais, estariam também sujeitos aos mesmos efeitos relativisticos.